2015
DOI: 10.2139/ssrn.2652234
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: The Age Dissimilarity between the Chair and the CEO

Abstract: A B S T R A C TWe study the relation between the chair of the board of directors and the CEO. We argue that substantial age dissimilarity between the two  giving rise to cognitive conflict  increases board monitoring and firm value for firms with greater monitoring needs. We find evidence for our hypothesis using data on German two-tier boards. German law mitigates endogeneity concerns as it prevents CEO duality and also restricts CEO power in other ways. Additional identification attempts include CEO-firm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 63 publications
2
34
0
3
Order By: Relevance
“…The distribution of the age difference is similar to the distribution of the age difference between the chairman and CEO of German listed firms studied by Goergen et al. [1] , which has certain theoretical significance for the correlation and regression analysis of age differences. The age dissimilarity reflects two notable characteristics.…”
Section: Data Descriptionsupporting
confidence: 81%
See 1 more Smart Citation
“…The distribution of the age difference is similar to the distribution of the age difference between the chairman and CEO of German listed firms studied by Goergen et al. [1] , which has certain theoretical significance for the correlation and regression analysis of age differences. The age dissimilarity reflects two notable characteristics.…”
Section: Data Descriptionsupporting
confidence: 81%
“…The main independent variable is the age dissimilarity between the chairman and CEO which is measured by three ways proposed by Goergen et al. [1] : Chair-CEO age gap, Chair-CEO age ratio, and Generational gap. The Chair-CEO age gap is the age of the chair minus the age of the CEO.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Roitto () reported a negative relationship between the average age of board members and CSR disclosure, whereas Katmon et al () reported no association between age diversity and QCSR disclosure. Goergen, Limbach, and Scholz () documented positive association between age diversity and board effectiveness and performance. Hence, on the basis of mixed results, we hypothesized the following:H1 Board age diversity is positively associated with QCSR disclosure.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this section, we explore a possible mechanism through which female boards increase firm value. Board meetings are the primary channel for directors to stay informed of a firm's operations, business conditions, and managerial decisions so that they can effectively participate in corporate governance (Brick & Chidambaran, 2010; Goergen, Limbach, & Scholz, 2015; Masulis et al, 2012). We thus focus on the number of board meetings as these meetings provide an important platform for directors to influence firm‐level decisions and the frequency of meeting signals directors' effort and diligence.…”
Section: Additional Tests and Robustness Checksmentioning
confidence: 99%